Bent Molecules with a 60° Central Core Angle that Form B7 and B2 Phases1. Issue 31 (24th June 2014) - Lee, Eun‐Woo; Takimoto, Koji; Tokita, Masatoshi; Watanabe, Junji; Kang, Sungmin
Abstract Small‐angle bent‐core liquid‐crystalline (LC) molecules based on a 1, 2‐bis(phenylethynyl)benzene central core have been synthesized that form banana smectic phases with a ferroelectric B7–antiferroelectric B2 phase sequence upon cooling. The formation of polar, switchable ferro‐/antiferroelectric banana phases indicates that, despite the low core bend angle of approximately 60°, banana smectic phases are still formed with the bend direction parallel to the layer. This study offers significant evidence that shows bent‐core molecules with a 60° bend angle can form the well‐known B2 and B7 banana phases. Consequently, it may lead to the preparation of a wide variety of novel bent molecules with low bend angles that spontaneously form an LC phase with both polarization and chirality.